Historical Data Reveal 30-Year Persistence of Benthic Fauna Associations in Heavily Modified Waterbody - Callaway, Ruth (Frontiers in Marine Science, 2016)
Baseline surveys form the cornerstone of coastal impact studies where altered conditions, for example through new infrastructure development, are assessed against a temporal reference state. They are snapshots taken before construction. Due to scarcity of relevant data prior to baseline surveys long-term trends can often not be taken into account. Particularly in heavily modified waterbodies this would however be desirable to control for changes in anthropogenic use over time as well as natural ecological variation. Here, the benthic environment of an industrialized embayment was investigated (Swansea Bay, Wales, UK) where it is proposed to build a tidal lagoon that would generate marine renewable energy from the tidal range. Since robust long-term baseline data was not available, the value of unpublished historical benthos information from 1984 by a regional water company was assessed with the aim to improve certainty about the persistence of current benthic community patterns. A survey of 101 positions in 2014 identified spatially discrete benthic communities with areas of high and low diversity. Habitat characteristics including sediment properties and the proximity to a sewage outfall explained 17-35% of the variation in the community structure. Comparing the historical information from 1984 with 2014 revealed striking similarity in the benthic communities between those years, not just in their spatial distribution but also to a large extent in the species composition. The 30-year-old information confirmed spatial boundaries of discrete species associations and pinpointed a similar diversity hotspot. A group of five common species was found to be particularly persistent over time (Nucula nitidosa, Spisula elliptica, Spiophanes bombyx, Nephtys hombergii, Diastylis rathkei). According to the Infauna Quality Index (IQI) linked to the EU Water Framework Directive (WFD) the average ecological status for 2014 was ‘moderate’, but eleven samples showing ‘poor’ and ‘bad’ status indicated possible negative impacts of dredge spoil disposal. Generally the study demonstrated the value of historical information for assessing the persistence of benthic community characteristics, while also highlighting shortcomings if raw data is lost and if the historical baseline does not reflect pristine ecological conditions.